2016
DOI: 10.1002/cam4.797
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants within microRNA‐binding site of RAD51B are associated with risk of cervical cancer in Chinese women

Abstract: RAD51B plays a central role in homologous recombinational repair (HRR) of DNA double‐strand breaks (DSBs), which is important to prevent genomic instability, a hallmark of cancer. Recent studies suggested that common genetic variants of RAD51B may contribute to cancer susceptibility. In this study, we aimed to investigate whether potentially functional variants within miRNA‐binding sites of RAD51B are associated with risk of cervical cancer. A total of 1486 cervical cancer patients and 1536 cancer‐free control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
(55 reference statements)
3
10
0
Order By: Relevance
“…RAD51B is one of the RAD51 gene families involved in homologous recombination-mediated DNA repair (Thacker, 2005;Nagathihalli and Nagaraju, 2011). Hang et al (2016) demonstrated that RAD51B is a tumor suppressor gene in cervical cancer cells, which is consistent with our prediction. They further showed that the miRNA binding sites of RAD51B genetic variants in cervical cancer cells may increase tumor susceptibility, and RAD51B is vital in gauging the cervical cancer risk of individuals and improving the effectiveness of preventive intervention (Hang et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…RAD51B is one of the RAD51 gene families involved in homologous recombination-mediated DNA repair (Thacker, 2005;Nagathihalli and Nagaraju, 2011). Hang et al (2016) demonstrated that RAD51B is a tumor suppressor gene in cervical cancer cells, which is consistent with our prediction. They further showed that the miRNA binding sites of RAD51B genetic variants in cervical cancer cells may increase tumor susceptibility, and RAD51B is vital in gauging the cervical cancer risk of individuals and improving the effectiveness of preventive intervention (Hang et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…The decreased expression of CXCL12 in cervical cancer cells and its role in lymph node metastasis was confirmed in previous experiments (Yadav et al, 2016), and the decreased expression of IGF1 and the increased expression of WDHD1 were also experimentally validated in cervical cancer cells but only in lymph node metastasis of other cancers (Serrano et al, 2006;Kümmel et al, 2007;Huang et al, 2008;Zhou et al, 2016;Liu et al, 2019). Interestingly, the expression of RAD51B is also decreased in cervical cancer cells, but experiments showed that its expression is increased in other cancer lymph node metastases (Cheng et al, 2016;Hang et al, 2016). In addition, REV3L expression is increased in cervical cancer cells and lymph node metastases of other cancers in the laboratory, which is inconsistent with our prediction results (Yang et al, 2015;Zhu et al, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…In gastric cancer, RAD51B specifically has been identified as a potential biomarker for poor prognosis [61]. Furthermore, genetic variants in miR-binding sites of RAD51B have been shown to be associated with cervical cancer risk [62]. While germline mutations in RAD51B do not contribute to CLL [63], lack of lncRNA expression may be contributing to RAD51B expression and thus contributing to disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, genotyping in the validation stage was performed using the Sequenom MassARRAY iPLEX platform (Sequenom Inc. San Diego, CA, USA) according to the protocol [15,16]. Primers for 17 out of 20 candidate SNPs were successfully constructed.…”
Section: Variants Validation Using Sequenom Platformmentioning
confidence: 99%